The museum makers : the story of the Royal Ontario Museum - Dickson, Lovat, 1902-1987 (Book collections on Project MUSE., 1986)
In the aftermath of World War II a new generation of museum men and women took up the challenge of keeping the Royal Ontario Museum one of the last combined science, art, and archaeology museums of first rank in the world. The unfolding story, with accomplishments, stresses, and strains interwoven, is captivating.